2015
DOI: 10.17654/jphmtfeb2015_001_028
|View full text |Cite
|
Sign up to set email alerts
|

Flow Patterns and Heat Transfer Around Six in-Line Circular Cylinders at Low Reynolds Number

Abstract: The flow field and the heat transfer around six in-line iso-thermal circular cylinders has been studied by mean of numerical simulations. Two values of the center to center

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…However, in case of forced convection the tighter spacing, s/d = 3.6, leads to a higher heat exchange. According to Fornarelli et al [6], such behaviour is related to an enhanced cold fluid entrainment in the gap between two successive cylinders for the s/d = 3.6 case, due to the near field flow oscillation (see fig. 5).…”
Section: Heat Exchange Performancementioning
confidence: 84%
See 1 more Smart Citation
“…However, in case of forced convection the tighter spacing, s/d = 3.6, leads to a higher heat exchange. According to Fornarelli et al [6], such behaviour is related to an enhanced cold fluid entrainment in the gap between two successive cylinders for the s/d = 3.6 case, due to the near field flow oscillation (see fig. 5).…”
Section: Heat Exchange Performancementioning
confidence: 84%
“…The refinement strategies include the limiting of the velocity and temperature difference between two adjacent grid cells every timestep. A detailed and comprehensive grid independence study and a sensitivity analysis on the domain dimension has been carried out as reported in a previous work of the authors [6]. At the inflow uniform flow is imposed with u = 1, v = 0 and T = 0, while at the outflow the spatial variation of the velocity components and temperature in the streamwise direction are imposed as follows: ∂u/∂x = 0, ∂v/∂x = 0 and The numerical results of the force coefficients and heat transfer coefficient are reported.…”
Section: Numerical Setupmentioning
confidence: 99%
“…Configuration of multiple array of cylinders has been discussed in several works. Effect of gap spacing on vortex shedding of laminar flow past six cylinders arranged in-line are studied by [4] and [5]. They found a flow pattern transition between spacing ratios 3.6 and 4 when drag and lift coefficients change significantly.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concern about pollutant emissions from coal promotes an efficiency improvement of the entire energy production technology. The optimization of the heat transfer in non-reacting parts [4][5][6] and the integration of renewable energy in conventional energy systems [7] represent just a few examples that indirectly reduce both the coal demand and the CO 2 emissions, for which computational fluid dynamics (CFD) has a key role. However, further developments are required to design low emission pulverized coal burners, characterized by low or negligible NO x emissions and ashes with a very low carbon content.…”
Section: Introductionmentioning
confidence: 99%